UNDERSTANDING THE DYNAMICS OF LIQUIDITY AND INFLATION ON ISLAMIC BANK PROFITABILITY IN INDONESIA - Firman Junaidi; Anggraeni Anggraeni (Nurul Jadid University, 2025)
This study investigates the impact of liquidity ratios on the profitability of Islamic banks in Indonesia, with inflation introduced as a moderating variable. Using a quantitative explanatory research design, the study analyzes secondary data from 11 Islamic banks over the 2021 to 2023 period. The liquidity indicators include the Cash Ratio, Quick Ratio, and Current Ratio, while Return on Assets (ROA) is used as a proxy for profitability. Inflation data is obtained from the national consumer price index. Multiple linear regression with interaction terms is employed to assess both direct and moderating effects. The classical assumption tests confirm that the model is free from normality violations, multicollinearity, autocorrelation, and heteroskedasticity. The regression results reveal that the Quick Ratio has a significant positive effect on profitability, while the Current Ratio has a significant negative impact. The Cash Ratio shows no significant influence on ROA. Inflation does not affect ROA directly but moderates the relationship between liquidity and profitability in two out of three indicators. The interaction between Quick Ratio and inflation is negative, while the interaction between Current Ratio and inflation is positive. These findings highlight the importance of adaptive liquidity strategies under varying macroeconomic conditions.